ENVIRONMENTAL TRAINING OF TUTOR: A CHALLENGE IN THE DECADE OF EDUCATION FOR SUSTAINABLE DEVELOPMENT - Aguiar Guillermo, Eulalio (Varela Journal, 2008)
In the context of teachers formation in Cuba, the tutor plays a fundamental role, because is the one that accompanies the future teachers in the heft of his/her studies in the micro-universities, being responsible for his/her integral formation, in which one the environmental formation is fundamental. Therefore it’s requiriered a capable teacher to develop in the students the creativity, the critical thought and that permits them to take right decisions related to the environmental problems to achieve the necessary transit towards the developmental sustainable education, however, tutors present insufficiencies to achieve these objectives, that’s why it’s necessary to elaborate a strategy for their environmental formation.